Toward 'Uhuru' in Tanzania the politics of participation - Maguire, G. Andrew (London Cambridge U.P, 1969)
In the belief that intensive study of selected local areas is an important development in scholarship on Africa, the author presents a micropolitical study of an important region of one of East Africa's Rew nations. Sukumaland, an area of Tanzania which contains one tenth of the country's population and its largest tribe, was chosen for the study. Before independence it exhibited the most organized nationalist political activity of any part of the country and developed the largest African-owned co-operative movement in all of Africa. In the final decade of the colonial era Sukumaland was the British administration's principal experimental area for attempts at radical transformation of indigenous political institutions and traditional agricultural techniques. After independence it became a critical testing ground for President Julius Nyerere's concepts of African socialism.
Bibliography: p. 385-392.
Keywords: Sukuma region